Estudo e projeto de um simulador de gerador fotovoltaico - Ricardo Lélis de Souza (2013)
This work consists of the study and design of a photovoltaic module generator simulator based on the control of a DC-DC Buck converter that emulates the photovoltaic output current of a commercial module with the purpose of facilitating tests in laboratory environment. These simulators replicate in laboratory the photovoltaic module behavior under the diverse environmental conditions to which they are subject, allowing repeated tests in any season of the year. The nominal characteristics of a photovoltaic module are modeled by an equation simulated on a computer, allowing the setting of a reference current to control a DCDC converter both for the nominal conditions of the studied module and for other incidental radiation and temperature values. From the modeling of the equation through simulation, two operating ways of the photovoltaic simulator are presented. In order to evaluate the photovoltaic simulator, the equation model is tested through simulation with DC Buck converter model. Tests are done to check the proper functioning of the converter and the results of this simulation validate the project for an implementation of the prototype in laboratory. The two operational ways are sent to a DSC Digital Signal Controller through a serial communication so that it emulates the reference current of the device is composed of a Buck converter and a voltage and current measurement board. To emulate the photovoltaic characteristics through the prototype, a converter control in current loop is suggested through a proportional-integral controller with saturation and pulse width modulation. The prototype elements are described and the results are graphically presented by the output charge variation, emulating the photovoltaic module.